Improving Knowledge and Skills of Early Mobilization among Post-Cesarean Section Mothers as an Effort to Accelerate Postoperative Recovery - Anita Sri Gandaria Purba; Pitriani Pitriani; Dian Anggriyanti; Ria Aprilia Waruwu; Abdi Lestari Sitepu (JURNAL PENGMAS KESTRA (JPK), 2026)
The increasing rate of Sectio Caesarea (SC) deliveries has highlighted the need for effective postoperative care to minimize complications and promote maternal recovery. Early mobilization is a recommended intervention; however, its implementation is often limited by inadequate maternal knowledge and practical skills. This community service program aimed to improve the knowledge and skills of post-Sectio Caesarea mothers regarding early mobilization to accelerate postoperative recovery, reduce the risk of complications, and enhance maternal independence during the postpartum period. The program adopted an educational-participatory approach incorporating health education, demonstrations, hands-on practice, and direct mentoring. Program effectiveness was evaluated using a one-group pretest-posttest design involving 20 post-Sectio Caesarea mothers at Grandmed Hospital, Lubuk Pakam. Participants' knowledge was assessed using structured questionnaires administered before and after the educational intervention, while practical skills were evaluated through direct observation using a standardized checklist. Participant satisfaction was also measured through a feedback questionnaire. The findings demonstrated a substantial improvement in participants' knowledge, with the proportion of mothers categorized as having good knowledge increasing from 15.0% before the intervention to 80.0% afterward, whereas the proportion with poor knowledge declined from 50.0% to 0%. Furthermore, 45.0% of participants achieved a very good skill level and 40.0% achieved a good skill level, indicating that 85.0% successfully performed early mobilization according to the recommended procedures. Participant satisfaction was highly positive, with 70.0% reporting being very satisfied and 30.0% satisfied with the program. In conclusion, an educational-participatory approach integrating health education, educational media, demonstrations, practical training, and mentoring effectively improved maternal knowledge, practical skills, and readiness to perform early mobilization safely, thereby supporting faster postoperative recovery and improving the quality of postpartum care.